2023
DOI: 10.1093/jpp/rgad063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of madecassoside in reducing oxidative stress and blood glucose in streptozotocin–nicotinamide-induced diabetes in rats

Abstract: Objectives Madecassoside (MAD) is a triterpenoid constituent of Centella asiatica (L.) Urb., an ethnomedical tropical plant, extracts of which were shown to reduce blood glucose in experimental diabetes. This study examines MAD for its anti-hyperglycaemic effects and tests the hypothesis that it reduces the blood glucose in experimentally induced diabetic rats by protecting the β-cells. Methods Diabetes was induced using stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In the present study, downregulation of levels of SOD, CAT and GSH suggested that the activity of the antioxidant enzyme system induced by bowel inflammation was suppressed, whereas this trend was reversed upon administering CUR, indicating recovery of the activity of the antioxidant enzyme defense system. In addition, MAD is a lipid peroxidation metabolite commonly used as a marker to measure lipid peroxidation metabolism in vivo , serving as an indicator to assess the generation of free radicals and damage they cause to the structure of the membrane lipid bilayer ( 47 ). In the present study, downregulation of MAD following CUR administration demonstrated elimination of oxidative stress mediated by CUR that occurred during inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, downregulation of levels of SOD, CAT and GSH suggested that the activity of the antioxidant enzyme system induced by bowel inflammation was suppressed, whereas this trend was reversed upon administering CUR, indicating recovery of the activity of the antioxidant enzyme defense system. In addition, MAD is a lipid peroxidation metabolite commonly used as a marker to measure lipid peroxidation metabolism in vivo , serving as an indicator to assess the generation of free radicals and damage they cause to the structure of the membrane lipid bilayer ( 47 ). In the present study, downregulation of MAD following CUR administration demonstrated elimination of oxidative stress mediated by CUR that occurred during inflammation.…”
Section: Discussionmentioning
confidence: 99%